Peningkatan Pengembangan Taman Mumbul dengan Community Based Tourism sebagai Wisata Spiritual di Desa Sangeh Badung - Pande, I Kadek Pande Maha Dwija; Sutama, I Kompiang Gede; Ximenes, Rui Ximenes; Prajanata, I Nyoman Oka; Setyawan, Putu Gita; Wirata, Gede Wirata (Penerbit Goodwood, 2024)
Purpose: The aim of making Mumbul Pancoran Solas Park a spiritual tourism destination in Sangeh Village, Badung Regency, which is not widely known, requires efforts to increase the development of various aspects to increase tourist visits by involving community participation based on community-based tourism to provide economic, social, and environmental sustainability impacts on local communities. Methodology: This research was conducted in Mumbul Pancoran Solas Park, Sangeh village, Abiansemal subdistrict, Badung Regency, using qualitative methods, data collection using observation, interviews, and documentation. Data analysis was carried out descriptively, analyzing the four ampere components (Attraction, Accessibility, Amenities, Ancillary) and SWOT analysis (Strength, Weakness, Opportunities, Threats). Results: The research results show that implementing community-based tourism (CBT) as an approach to tourism development, community empowerment in socio-cultural economic terms, establishing cooperation, and forming tourism awareness groups. Mumbul Pancoran Solas Park, Sangeh Village, has the advantage of natural tourism which is also an environmental conservation effort and is able to provide economic benefits to the local community. In addition, it is necessary to improve infrastructure to support tourism activities so that good tourism governance can be formed. The development of Mumbul Pancoran Solas Park with the Pancoran Solas icon (11) is an important element in the development of this tourist attraction, so that development can be carried out holistically and sustainably. Limitations: Due to the limited time and objects in this research and the implementation of the activity for one day, it is hoped that it will be sustainable and provide the benefit of contributing ideas. Contribution: This community service is a strategy to increase efforts to develop spiritual tourism by empowering the Sangeh village community and providing managerial skills to the tourism manager of Mumbul Pancoran Solas Park.